"To be One Heart and Soul in God". Augustine on Peace within the Family - van Egmond, Bart (Editorial Uniagustiniana, 2019)
This essay describes how Augustine conceives of peace within the marriage of man and woman. According to Augustine, true peace is found where humans love the same goods in the right way. How does that work in marriage? First, the essay depicts the decline of the traditional understanding of marriage in Western societies. Subsequently, it treats Augustine's view of "marital peace" in three stages: before the fall, its corruption after the fall, and its redemption by divine grace. A final section answers the question: What present-day Christians can relearn from Augustine with regard to a peaceful relationship between husband and wife?